2015
DOI: 10.1111/bcp.12649
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of tacrolimus in Mexican paediatric renal transplant patients: role of CYP3A5 genotype and formulation

Abstract: AIMSThe aims of this study were (i) to develop a population pharmacokinetic (PK) model of tacrolimus in a Mexican renal transplant paediatric population (n = 53) and (ii) to test the influence of different covariates on its PK properties to facilitate dose individualization. METHODSPopulation PK and variability parameters were estimated from whole blood drug concentration profiles obtained at steady-state using the non-linear mixed effect modelling software NONMEM® Version 7.2. RESULTSTacrolimus PK profiles ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…For these reasons, it was decided that generic formulations, administered to patients included in the present study, had to be classified based on corresponding blood trough concentrations corrected by dose of tacrolimus to determine the relative bioavailability among generic formulations. This resulted in a higher bioavailability of Framebin ® than Limustin ® , demonstrating that generic formulations of tacrolimus are not interchangeable and switching between them will result in significant changes in blood concentrations; therefore, critical clinical attention and therapeutic monitoring are required …”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it was decided that generic formulations, administered to patients included in the present study, had to be classified based on corresponding blood trough concentrations corrected by dose of tacrolimus to determine the relative bioavailability among generic formulations. This resulted in a higher bioavailability of Framebin ® than Limustin ® , demonstrating that generic formulations of tacrolimus are not interchangeable and switching between them will result in significant changes in blood concentrations; therefore, critical clinical attention and therapeutic monitoring are required …”
Section: Discussionmentioning
confidence: 99%
“…In only 13.8% of the studies (N = 4), CYP3A5*3 variants were categorized into 3 groups: CYP3A5*1*1, *1*3, and *3*3, which were defined as extensive, intermediate, and poor metabolizers. 37,47,48,58 The fractional change in the average tacrolimus clearance was 1.39 (range 1.18-1.69) for intermediate and 1.8 (range 1.25-2.0) for extensive metabolizers compared to that of poor metabolizers. Across all the studies that investigated the CYP3A5*3 variant, the frequencies of the wild-type *1*1, heterozygous *1*3, and homozygous *3*3 were not equal.…”
Section: Population Pharmacokinetic Model Structure and Final Covariatesmentioning
confidence: 97%
“…16,32,33 With increased use of tacrolimus minimization protocols, newer immunoassays such as chemiluminescent microparticle immunoassay (N = 10) were introduced and provided improved sensitivity to less than 1 ng/mL with enhanced specificity. [34][35][36][37][38][39][40] In the remaining studies (ß30%), the assays conducted used a liquid chromatographic method coupled with mass spectrometry, which provides lower sensitivity and improved specificity but has limited availability at many centers ( Figure 2E). Assay methodology was not found to be a significant covariate.…”
Section: Tacrolimus Pharmacokinetic Sampling Sample Matrix Andmentioning
confidence: 99%
“…It has been reported that non‐innovator formulations from several emerging not highly regulated, countries, including Mexico, do not meet the quality criteria established for the innovator, including the dissolution profile . Moreover, previous studies from our research group have shown that some low‐quality tacrolimus formulations result in a lower bioavailability in children . Hence, if an LSS is going to be implemented for pediatric patients, including those from emerging countries, its ability to predict the tacrolimus AUC in all available formulations is of crucial importance.…”
Section: Introductionmentioning
confidence: 98%